Wetting of graphite by molten Cu–xSn–yCr ternary alloys at 1373 K. (15th April 2020) - Lin, Qiaoli; Yang, Fan; Yang, Hongyu; Sui, Ran; Shi, Yu; Wang, Jianbin
Abstract: This paper presents an experimental approach where the effect of Cr and Sn concentrations on the wetting of graphite by molten Cu- x Sn- y Cr ternary alloys at 1373 K. It shows that a small quantity of Cr addition (≤2 at.%) can improve the wettability significantly owing to the formation of chromium carbides at the interface. Sn addition ( x ≤ 30 at.%) can further improve the wettability by decreasing the surface tension. However, higher Sn concentration ( x ≥ 40 at.%) will cause the precipitation of main phase at the interface, varying from Cr7 C3 to Cr3 C2, which in turn will slightly deteriorate the wettability. The phase equilibrium transition point ( x ≈ 35% in Cu– x Sn–1Cr/Cgraphite ) is responsible for wettability variation by the increase of Sn concentration. When the Sn concentration is ≥ 40 at.%, the spreading dynamics are satisfied with the assumption of the classical diffusion-limited spreading model. When the Sn concentration is ≤ 30 at.%, the transport route of Cr is from the Sn segregation layer on the drop surface to the triple line rather than from the internal diffusion of the bulk drop to the triple line, and then a precursor film with the specific width can be formed. Highlights: Transition of reaction product coupled wettability of Cu- x Sn-1Cr/Cgraphite at x ∼ 35 at.%. The formed precursor film was induced both by decreased surface tension and high affinity at interface. Diffusion-limited reactive spreading model described the wetting behavior.